Optimizing classroom acoustics using computer model studies - Reich, Rebecca; Bradley, John (Canadian Acoustics, 1998)
Speech intelligibility in rooms is determined by both room acoustics characteristics as well as speech-to-noise ratios. These two types of effects are combined in measures such as useful-to-detrimental sound ratios which are directly related to speech intelligibility. This paper reports investigations of optimum acoustical conditions for classrooms using the ODEON room acoustics computer model. By determining conditions that relate to maximum useful-to-detrimental sound ratios, optimum conditions for speech are determined. The results show that an optimum mid-frequency reverberation time for a classroom is approximately 0.5 s, but speech intelligibility is not very sensitive to small deviations from this optimum. Speech intelligibility is influenced more strongly by ambient noise levels. The optimum location of sound absorbing material was found to be on the upper parts of the walls.